A Digital Twin Ocean: can we improve coastal ocean forecasts using targeted marine autonomy? - Dale Partridge; Deep Banerjee; David Ford; Ke Wang; Jozef Skákala; Juliane Wihsgott; Prathyush P. Menon; Susan Kay; Daniel Clewley; Andrea Rochner; Emma Sullivan; Matthew Palmer (Ocean Science, 2026)
This study outlines the development and testing of a Digital Twin Ocean (DTO) framework, aimed at improving coastal ocean forecasts through the use of autonomous underwater gliders. A fleet of gliders were deployed in the western English Channel during August-September 2024 to collect measurements of temperature, salinity, chlorophyll and oxygen, aiming to track the movement of the harmful algal bloom Karenia mikimotoi. Measurements were assimilated into a very high resolution (1.5 km) numerical forecast model, with an implementation of biogeochemistry data assimilation for this purpose. The model forecast was then used by a probabilistic uncertainty model to plan a series of waypoints to navigate the glider fleet towards features of interest. By utilising a continuous feedback loop of measurement, prediction, guidance, and refinement a system with real time coupling between the real ocean environment and its digital counterpart has been established. Building upon a prior pilot study of Ford et al. (2022), this work improves every element of the system to address several limitations of the prior configuration. Whilst a bloom was present in the wider area, measurements and modeling suggest it didn't enter the glider operation zone. Despite this and other operational challenges the mission clearly demonstrates the benefits of such a system. The ability to simultaneously track multiple features of interest, namely chlorophyll maxima and oxygen minima, would not have been possible with a single glider resulting in significant benefits to the system. Furthermore, the improvement to biogeochemical forecasting has been demonstrated through a series of post mission experiments, highlighting the advantages of high temporal resolution observations and increased spatial resolution of the model.

Navigating tricky trade-offs in busy seas: Insights from England for blue justice - Matt Fortnam; Liliana Bastian; Angela Phan; Océane Marcone; Tomas Chaigneau; Susan Kay; Sarah Sutcliffe; Rachel A Turner; Ruby Grantham; Aisling Lannin; Louisa Evans (Marine Policy, 2026)

Marine data assimilation in the UK: the past, the present, and the vision for the future - Jozef Skákala; David Ford; Keith Haines; Amos Lawless; Matthew J. Martin; Philip Browne; Marcin Chrust; Stefano Ciavatta; Alison Fowler; Daniel Lea; Matthew Palmer; Andrea Rochner; et al. (Ocean Science, 2025)
In the last 2 decades, UK research institutes have led a wide range of developments in marine data assimilation (MDA), covering areas from operational applications in physics and biogeochemistry to fundamental theory. We highlight the emergence of strong collaboration in the UK MDA community over this period and the increasing unification of its tools. We focus on identifying the MDA stakeholder community and current/future areas of impact, as well as current trends and future opportunities. This includes the rapid growth of machine learning (ML)/artificial intelligence (AI) and digital-twin applications. We articulate a vision for the future, including the need for future types of observational data (whether planned missions or hypothetical) and how the community should respond to increases in computational power and new computer architectures (e.g. exascale computing). We contrast the requirements of different MDA areas, including physics, biogeochemistry, and coupled data assimilation (DA). Although the specifics of the vision depend on each area, common themes emerge. We advocate for balanced redistribution of new computational capability among increased model resolution, model complexity, more sophisticated DA algorithms, and uncertainty representation (e.g. ensembles). We also advocate for integrated approaches, such as strongly coupled DA (ocean–atmosphere, physics–biogeochemistry, and ocean–sea ice) and the use of ML/AI components (e.g. for multivariate increment balancing, bias correction, model emulation, observation re-gridding, or fusion).

Measuring Dietary Quality Among Toddlers in the Feeding Infants and Toddlers Study, 2016, Using the New Healthy Eating Index-Toddlers-2020 - Melissa C. Kay; Joel Hampton; Susan Pac; Lyndsey Huss; Alison L. Eldridge (Journal of the Academy of Nutrition and Dietetics, 2025)

Multiple Models of European Marine Fish Stocks: Regional Winners and Losers in a Future Climate - Sévrine F. Sailley; Ignacio A. Catalan; Jurgen Batsleer; Sieme Bossier; Dimitrios Damalas; Cecilie Hansen; Martin Huret; Georg Engelhard; Katell Hamon; Susan Kay; Francesc Maynou; J. Rasmus Nielsen; et al. (Global Change Biology, 2025)
Climate change continues to alter the productivity of commercially and culturally important fisheries with major consequences for food security and coastal economies. We provide the first, multi‐model projections of changes in the distribution and productivity of 18 key fish stocks across seven European regional seas spanning the Mediterranean to the Arctic, using 11 state‐of‐the‐art bio‐ecological models. Our projections indicate species‐ and region‐specific changes in abundance and distributions of these stocks by the mid‐ to late 21st century. The varied responses are caused by differences in species' physiology, regional food web dynamics, and physical habitat characteristics. Important drivers include not only warming of Europe's seas (from 1°C to 3°C in RCP 4.5, and 2°C to 4°C in RCP 8.5 by 2100) and changes in primary productivity but also oxygen‐limited fish growth, changes in pH, and benthic dissolved organic carbon. Warming and altered levels of secondary production are projected to lead to declines in some stocks (Norwegian and Barents Sea herring) and increases in others (Bay of Biscay anchovy). While some temperate and cold‐water stocks are projected to decline markedly in some regions (e.g., North Sea, Western Mediterranean), the immigration of species from the south and/or increase in productivity of warm‐water species may offer new opportunities for fisheries. Species‐level changes will likely have ecosystem‐level consequences that have yet to be fully assessed, and responses in some sub‐areas may be more pronounced due to local processes not captured in projections. Projections are consistent despite differences in model structures, and the results of our multi‐model analysis align with other modelling exercises while delving into details often overlooked at the species or spatial level. This represents a novel approach to projecting the impacts of climate change on fisheries, which should be considered in future efforts to support climate‐ready management strategies for marine fish stocks.

Incorporating climate-readiness into fisheries management strategies - Elizabeth Talbot; Jean-Beth S. Jontila; Benjamin J. Gonzales; Roger G. Dolorosa; Edgar D. Jose; Recca Sajorne; Sevrine Sailley; Susan Kay; Ana M. Queirós (Science of The Total Environment, 2024)

Planning precision aquaculture activities in a changing and crowded sea - M. Cristina Mangano; Laura Corbari; Antonio Giacoletti; Manuel Berlino; Susan Kay; Giuseppe Ciraolo; Gianluca Sarà (Aquaculture, 2023)

Climate change projections of commercial fish distribution and suitable habitat around north western Europe - Bryony L. Townhill; Elena Couce; Jonathan Tinker; Susan Kay; John K. Pinnegar (Fish and Fisheries, 2023)
Under future climate change, modification of temperature and salinity are expected to result in distribution shifts of marine organisms, including commercial fish and shellfish. Changes are anticipated everywhere, including in the seas of many important fishing nations. Species turnover will in turn result in both opportunities and threats to fishing industries. To determine the impacts for northwest European shelf fisheries, we project changes for 49 commercially important fish and shellfish species using an ensemble of five ecological niche models and three different downscaled climate change projections. The habitat suitability and latitudinal shifts projected from the recent past (1997–2016) to two futures (2030–2050; 2050–2070) were calculated for waters around the United Kingdom. Of the species examined, around half were projected to have consistently more suitable habitat in the future, including European seabass ( Dicentrarchus labrax , Moronidae), sardine ( Sardina pilchardus , Alosidae) and anchovy ( Engraulis encrasicolus , Engraulidae). Conversely, it is suggested that UK waters will become less suitable for species including Atlantic cod ( Gadus morhua , Gadidae) and saithe ( Pollachius virens , Gadidae). Our comprehensive approach using a number of models and climate change scenarios shows that while there are differences in the magnitude of change between models, and while some models perform better for certain species compared with others, overall, the general trends in habitat suitability and abundance are robust across models and climate scenarios. This emphasises the value in using more than one modelling technique with different climate scenarios (i.e., an ensemble approach) to capture the uncertainty or agreement around climate change projections.

Projected effects of climate change on marine ecosystems in Southeast Asian seas - Susan Kay; Arlene L. Avillanosa; Victoria V. Cheung; Hung N. Dao; Benjamin Jareta Gonzales; Herminie P. Palla; Radisti A. Praptiwi; Ana M. Queirós; Sévrine F. Sailley; Joel D. C. Sumeldan; Wan Mohd Syazwan; Amy Yee-Hui Then; et al. (Frontiers in Marine Science, 2023)
The seas of Southeast Asia are home to some of the world’s most diverse ecosystems and resources that support the livelihoods of millions of people. Climate change will bring temperature changes, acidification and other environmental change, with uncertain consequences for human and natural systems, but there has been little regional-scale climate modelling of the marine ecosystem. We present initial dynamically downscaled projections using a biogeochemical model suitable for coastal and shelf seas. A coupled physical-biogeochemical model with a resolution of 0.1° (approximately 11 km) was used to create projections of future environmental conditions under moderate (RCP4.5) and high (RCP8.5) greenhouse gas scenarios. Changes for different parts of the region are presented, including four sensitive coastal sites of key importance for biodiversity and sustainable development: UNESCO Biosphere Reserves at Cu Lao Cham-Hoi An in Vietnam, Palawan in the Philippines and Taka Bonerate-Kepulauan Selayar in Indonesia, and coastal waters of Sabah, Malaysia, which include several marine parks. The projections show a sea that is warming by 1.1 to 2.9°C through the 21st century, with dissolved oxygen decreasing by 5 to 13 mmol m -3 and changes in many other environmental variables. The changes reach all parts of the water column and many places are projected to experience conditions well outside the range seen at the start of the century. The resulting damage to coral reefs and altered species distribution would have consequences for biodiversity, the livelihoods of small-scale fishers and the food security of coastal communities. Further work using a range of global models and regional models with different biogeochemical components is needed to provide confidence levels, and we suggest some ways forward. Projections of this type serve as a key tool for communities and policymakers as they plan how they will adapt to the challenge of climate change.

Quantifying cancer risk from exposures to medical imaging in the Risk of Pediatric and Adolescent Cancer Associated with Medical Imaging (RIC) Study: research methods and cohort profile - Marilyn L. Kwan; Diana L. Miglioretti; Erin J. A. Bowles; Sheila Weinmann; Robert T. Greenlee; Natasha K. Stout; Alanna Kulchak Rahm; Susan A. Alber; Priscila Pequeno; Lisa M. Moy; Carly Stewart; Cindy Fong; et al. (Cancer Causes & Control, 2022)

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Bright spots as climate‐smart marine spatial planning tools for conservation and blue growth - Ana M. Queirós; Elizabeth Talbot; Nicola J. Beaumont; Paul J. Somerfield; Susan Kay; Christine Pascoe; Simon Dedman; Jose A. Fernandes; Alexander Jueterbock; Peter I. Miller; Sevrine F. Sailley; Gianluca Sará; et al. (Global Change Biology, 2021)
Marine spatial planning that addresses ocean climate‐driven change (‘climate‐smart MSP’) is a global aspiration to support economic growth, food security and ecosystem sustainability. Ocean climate change (‘CC’) modelling may become a key decision‐support tool for MSP, but traditional modelling analysis and communication challenges prevent their broad uptake. We employed MSP‐specific ocean climate modelling analyses to inform a real‐life MSP process; addressing how nature conservation and fisheries could be adapted to CC. We found that the currently planned distribution of these activities may become unsustainable during the policy's implementation due to CC, leading to a shortfall in its sustainability and blue growth targets. Significant, climate‐driven ecosystem‐level shifts in ocean components underpinning designated sites and fishing activity were estimated, reflecting different magnitudes of shifts in benthic versus pelagic, and inshore versus offshore habitats. Supporting adaptation, we then identified: CC refugia (areas where the ecosystem remains within the boundaries of its present state); CC hotspots (where climate drives the ecosystem towards a new state, inconsistent with each sectors’ present use distribution); and for the first time, identified bright spots (areas where oceanographic processes drive range expansion opportunities that may support sustainable growth in the medium term). We thus create the means to: identify where sector‐relevant ecosystem change is attributable to CC; incorporate resilient delivery of conservation and sustainable ecosystem management aims into MSP; and to harness opportunities for blue growth where they exist. Capturing CC bright spots alongside refugia within protected areas may present important opportunities to meet sustainability targets while helping support the fishing sector in a changing climate. By capitalizing on the natural distribution of climate resilience within ocean ecosystems, such climate‐adaptive spatial management strategies could be seen as nature‐based solutions to limit the impact of CC on ocean ecosystems and dependent blue economy sectors, paving the way for climate‐smart MSP.

Impact of Seawater Temperature on Coral Reefs in the Context of Climate Change. A Case Study of Cu Lao Cham – Hoi An Biosphere Reserve - Hung N. Dao; Hang T. Vu; Susan Kay; Sevrine Sailley (Frontiers in Marine Science, 2021)
Coral reefs are a natural habitat for many species, as well as being of high economic and touristic significance. However, they represent an extremely sensitive ecosystem with a narrow ecological limit: prolonged high temperatures can lead to bleaching, in which corals expel their symbiotic algae and eventually corals will degrade and die. Based on climate change projections from the Blue Communities regional model, using linear regression, exponential regression, polynomial regression, we found that by the decades 2041–2050 and 2051–2060, whether with RCP 4.5 or RCP 8.5, the environmental temperature will change beyond the coral capacity threshold. Of particular concern is RCP 8.5, where the number of weeks per decade in which SST exceeds the threshold of coral reef bleaching is up to 55, compared to 0 at the beginning of the century. As well, the El Niño phenomenon often heats up waters to abnormally high temperatures in Cu Lao Cham and, it is projected to rise even further. Consequently, the combination of climate change and El Niño will cause abnormal increases in the seawater environment beyond the coral resistance threshold, leading to degradation of this internationally important site. Decisive and practical action must be taken to deal with climate change in this part of the world.

Direct effects of climate change on productivity of European aquaculture - Alhambra Martínez Cubillo; João G. Ferreira; João Lencart-Silva; Nick G.H. Taylor; Adam Kennerley; James Guilder; Susan Kay; Pauline Kamermans (Aquaculture International, 2021)

Assessment of the Skill of Coupled Physical–Biogeochemical Models in the NW Mediterranean - Eduardo Ramirez-Romero; Gabriel Jordà; Angel Amores; Susan Kay; Mariona Segura-Noguera; Diego M. Macias; Francesc Maynou; Ana Sabatés; Ignacio A. Catalán (Frontiers in Marine Science, 2020)

From Observation to Information and Users: The Copernicus Marine Service Perspective - Pierre Yves Le Traon; Antonio Reppucci; Enrique Alvarez Fanjul; Lotfi Aouf; Arno Behrens; Maria Belmonte; Abderrahim Bentamy; Laurent Bertino; Vittorio Ernesto Brando; Matilde Brandt Kreiner; Mounir Benkiran; Thierry Carval; et al. (Frontiers in Marine Science, 2019)

Inferring infection hazard in wildlife populations by linking data across individual and population scales - Kim M. Pepin; Shannon L. Kay; Ben D. Golas; Susan S. Shriner; Amy T. Gilbert; Ryan S. Miller; Andrea L. Graham; Steven Riley; Paul C. Cross; Michael D. Samuel; Mevin B. Hooten; Jennifer A. Hoeting; et al. (Ecology Letters, 2017)
Our ability to infer unobservable disease‐dynamic processes such as force of infection (infection hazard for susceptible hosts) has transformed our understanding of disease transmission mechanisms and capacity to predict disease dynamics. Conventional methods for inferring FOI estimate a time‐averaged value and are based on population‐level processes. Because many pathogens exhibit epidemic cycling and FOI is the result of processes acting across the scales of individuals and populations, a flexible framework that extends to epidemic dynamics and links within‐host processes to FOI is needed. Specifically, within‐host antibody kinetics in wildlife hosts can be short‐lived and produce patterns that are repeatable across individuals, suggesting individual‐level antibody concentrations could be used to infer time since infection and hence FOI . Using simulations and case studies (influenza A in lesser snow geese and Yersinia pestis in coyotes), we argue that with careful experimental and surveillance design, the population‐level FOI signal can be recovered from individual‐level antibody kinetics, despite substantial individual‐level variation. In addition to improving inference, the cross‐scale quantitative antibody approach we describe can reveal insights into drivers of individual‐based variation in disease response, and the role of poorly understood processes such as secondary infections, in population‐level dynamics of disease.

Solutions for ecosystem‐level protection of ocean systems under climate change - Ana M. Queirós; Klaus B. Huebert; Friedemann Keyl; Jose A. Fernandes; Willem Stolte; Marie Maar; Susan Kay; Miranda C. Jones; Katell G. Hamon; Gerrit Hendriksen; Youen Vermard; Paul Marchal; et al. (Global Change Biology, 2016)
The Paris Conference of Parties ( COP 21) agreement renewed momentum for action against climate change, creating the space for solutions for conservation of the ocean addressing two of its largest threats: climate change and ocean acidification ( CCOA ). Recent arguments that ocean policies disregard a mature conservation research field and that protected areas cannot address climate change may be oversimplistic at this time when dynamic solutions for the management of changing oceans are needed. We propose a novel approach, based on spatial meta‐analysis of climate impact models, to improve the positioning of marine protected areas to limit CCOA impacts. We do this by estimating the vulnerability of ocean ecosystems to CCOA in a spatially explicit manner and then co‐mapping human activities such as the placement of renewable energy developments and the distribution of marine protected areas. We test this approach in the NE Atlantic considering also how CCOA impacts the base of the food web which supports protected species, an aspect often neglected in conservation studies. We found that, in this case, current regional conservation plans protect areas with low ecosystem‐level vulnerability to CCOA , but disregard how species may redistribute to new, suitable and productive habitats. Under current plans, these areas remain open to commercial extraction and other uses. Here, and worldwide, ocean conservation strategies under CCOA must recognize the long‐term importance of these habitat refuges, and studies such as this one are needed to identify them. Protecting these areas creates adaptive, climate‐ready and ecosystem‐level policy options for conservation, suitable for changing oceans.

Projected changes in area of the Sundarban mangrove forest in Bangladesh due to SLR by 2100 - Andres Payo; Anirban Mukhopadhyay; Sugata Hazra; Tuhin Ghosh; Subhajit Ghosh; Sally Brown; Robert J. Nicholls; Lucy Bricheno; Judith Wolf; Susan Kay; Attila N. Lázár; Anisul Haque (Climatic Change, 2016)

Polymorphisms in genes related to one-carbon metabolism are not related to pancreatic cancer in PanScan and PanC4 - Max Leenders; Samsiddhi Bhattacharjee; Paolo Vineis; Victoria Stevens; H. Bas Bueno-de-Mesquita; Xiao-Ou Shu; Laufey Amundadottir; Myron Gross; Geoffrey S. Tobias; Jean Wactawski-Wende; Alan A. Arslan; Eric J. Duell; et al. (Cancer Causes & Control, 2013)

Environmental and seasonal influences on red raspberry flavour volatiles and identification of quantitative trait loci (QTL) and candidate genes - Alistair Paterson; Angzzas Kassim; Susan McCallum; Mary Woodhead; Kay Smith; Dzeti Zait; Julie Graham (Theoretical and Applied Genetics, 2013)

Oncologists’ Confidence in Knowledge of Fertility Issues for Young Women with Cancer - Christine Duffy; Susan M. Allen; Catherine Dube; Kay Dickersin (Journal of Cancer Education, 2012)

Candidate Screening of the TRPC3 Gene in Cerebellar Ataxia - Esther B. E. Becker; Brent L. Fogel; Sanjeev Rajakulendran; Anna Dulneva; Michael G. Hanna; Susan L. Perlman; Daniel H. Geschwind; Kay E. Davies (The Cerebellum, 2011)

Mapping QTLs for developmental traits in raspberry from bud break to ripe fruit - Julie Graham; Christine A. Hackett; Kay Smith; Mary Woodhead; Ingo Hein; Susan McCallum (Theoretical and Applied Genetics, 2009)

A Comparative Test of Adaptive Explanations for Hypsodonty in Ungulates and Rodents - Susan H. Williams; Richard F. Kay (Journal of Mammalian Evolution, 2001)